MAQĀṢID HUKUM KELUARGA ISLAM DALAM KOMPILASI HUKUM ISLAM (KHI) - Maulanida; Syafi'ie, Ahmad Musta'in (LPPM STAI Muhammadiyah Probolinggo, 2024)
The concept of maqāṣid encompasses more than just the well-known maqāṣid of Shariah, which includes the five essentials: protecting life, religion, intellect, lineage, and property. Scholars from the 6th century Hijri formulated these maqāṣid using the method of istiqra’ ma’nawi, which allows for content analysis across various texts, including positive law. This research applies this method to the Compilation of Islamic Law (KHI), which serves as a legal guide for judges in Indonesian religious courts. The objective is to identify the maqāṣid of Islamic family law within the KHI. The study found 120 maqāṣid of family law through analyses of illat, munāsabah, and characteristics in articles 1-170 of the KHI. From these findings, seven maqāṣid kulliyah of Islamic family law in KHI were concluded: (1) maintaining the continuity of law and agreements; (2) supervising legal actions related to family; (3) providing legal documents; (4) ensuring the welfare of the parties involved; (5) activating the roles of all parties in legal actions; (6) responding to family law cases; and (7) promoting noble values in family life. Keywords: Maqāṣid Qānūn; Shariah Objectives; Istikhrāj Maqāṣid; Islamic Family Law; KHI.